Formation of Character for Orphan Children at The Darul Hadlonah Orphanage Purwodadi Grobogan - Noviyati, N; Ulfatun, Titik (Proceedings International Conference on Education Innovation and Social Science, 2024)
The purpose of this study is first to explore the factors that influence the formation of orphans' character, second is to explain how to form the character of orphans when viewed from the aspects of discipline and honesty and finally describes the way guardians as caregivers of orphans in the formation at the Darul Hadlonah Purwodadi Grobogan Orphanage. This study is a qualitative study. Data collection techniques used include observation, interviews, and document analysis. The data analysis technique used is an interactive data analysis technique and is carried out continuously. The results of the study indicate that the formation of the character of orphans at the Darul Hadlonah Orphanage is influenced by: a) social environment; b) education and learning; c) emotional and psychological support; d) physical conditions and facilities; e) instilling honest and disciplined characters. How to form character through discipline and honesty, namely: a) discipline as the foundation for character formation; b) honesty in the context of character education; c) education and learning through extracurricular activities; d) emotional and psychological support as supporting factors. The role of caregivers in character formation: a) formation of morals; b) habits of clean living; c) role models in discipline; d) respect yourself and others; e) integration of worship in daily life.